Impact of Earning Volatility, Real Earnings Management and Accruals on Investment Policy: Evidence From Indonesia - I Dewa Made Endiana; Putu Diah Kumalasari (Jurnal Keuangan dan Perbankan, 2022)
This study aims to analyze earnings volatility, real earnings management activities, and accruals on the company's investment policy. The sample used is manufacturing companies on the Indonesian stock exchange as many as 117 companies with a total of 351 observations during the 2018-2020 period. This study used 2 models, each of which was tested using linear regression. The results showed that earnings volatility increased management motivation in carrying out accrual earnings management practices and real earnings management through the manipulation of production costs by managers, but the effect of greater volatility was found in the real earnings management model. Accrual earnings management has an effect on the company's over-under investment policy, while real earnings management through operating cash flow and production costs has no significant effect on investment policy. Accrual earnings management is able to increase the company's over-under investment policy